Intact neurological survival after emergency caesarean delivery for pathological fetal heart rate tracings at term- is it time to rethink ‘fetal distress’ interpretation of cardiotocography in South African cerebral palsy lawsuits? - Van Rooyen, Donée (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMed) -- Stellenbosch University, 2023.